Experimental study on the moisture removal of a 450-mm FOUP during the purge or vacuum process. (5th September 2016) - Hu, Shih-Cheng; Huang, Zhe-Yu; Fu, Ben-Ran
Highlights: The moisture removal is accelerated as the purge flowrate increases. Purging with flow distributors enhances the performance of the moisture removal. The difference in the RH of each location during the vacuum process is insignificant. The RH decreases rapidly and linearly during the vacuum process. The correlations of the RH evolution are proposed in the different form. Abstract: Due to the prodigious advances in semiconductor technology, the chip size has been dramatically reduced and, therefore, the rigorous limitation of contaminations (such as particle and moisture) on the wafer during the fabrication and transportation is required. A front opening unified pod (FOUP) is a portable container for the silicon wafers. This study investigates the moisture removal of a next-generation 450-mm FOUP during the purge (using clean dry air as the purge gas) or the vacuum process. The experimental results show that the performance of the moisture removal are significantly improved and uniformly distributed in the FOUP for the higher purge flowrates; purging with flow distributors significantly accelerates the moisture removal of the FOUP; unlike the purge method, the difference in the relative humidity (RH) of each location during the vacuum process is insignificant and the RH decreases rapidly and linearly. The correlations of the RH during the purge and vacuum processes are further proposed in the form of the exponential and linear decrease, respectively. For most of the studied cases, the performance of the moisture removal can be reached to 95% within 180 s. The vacuum method and purge method with flow distributors at the purge flowrate of 360 l/min require the shortest time (i.e., 90 s) to reach the removal performance of 95%. Moreover, if a rigorous limitation of the RH is needed, such as RH = 0, the vacuum method might be the most promising approach.